Spatial organization of bacterial transcription and translation - Castellana, Michele (Proc Natl Acad Sci U S A, 2016)
In bacteria such as Escherichia coli, DNA is compacted into a nucleoid near the cell center, whereas ribosomes—molecular complexes that translate mRNAs into proteins—are mainly localized to the poles. We study the impact of this spatial organization using a minimal reaction–diffusion model for the cellular transcriptional–translational machinery. Although genome-wide mRNA-nucleoid segregation still lacks experimental validation, our model predicts that [Formula: see text] of mRNAs are segregated to the poles. In addition, our analysis reveals a “circulation” of ribosomes driven by the flux of mRNAs, from synthesis in the nucleoid to degradation at the poles. We show that our results are robust with respect to multiple, biologically relevant factors, such as mRNA degradation by RNase enzymes, different phases of the cell division cycle and growth rates, and the existence of nonspecific, transient interactions between ribosomes and mRNAs. Finally, we confirm that the observed nucleoid size stems from a balance between the forces that the chromosome and mRNAs exert on each other. This suggests a potential global feedback circuit in which gene expression feeds back on itself via nucleoid compaction.